Rocahepevirus ratti as an Emerging Cause of Acute Hepatitis Worldwide - Sara Benavent; Silvia Carlos; Gabriel Reina (Microorganisms, 2023)
The hepatitis E virus (HEV) is a widespread human infection that causes mainly acute infection and can evolve to a chronic manifestation in immunocompromised individuals. In addition to the common strains of hepatitis E virus (HEV-A), known as Paslahepevirus balayani, pathogenic to humans, a genetically highly divergent rat origin hepevirus (RHEV) can cause hepatitis possessing a potential risk of cross-species infection and zoonotic transmission. Rocahepevirus ratti, formerly known as Orthohepevirus C, is a single-stranded RNA virus, recently reassigned to Rocahepevirus genus in the Hepeviridae family, including genotypes C1 and C2. RHEV primarily infects rats but has been identified as a rodent zoonotic virus capable of infecting humans through the consumption of contaminated food or water, causing both acute and chronic hepatitis cases in both animals and humans. This review compiles data concluding that 60% (295/489) of RHEV infections are found in Asia, being the continent with the highest zoonotic and transmission potential. Asia not only has the most animal cases but also 16 out of 21 human infections worldwide. Europe follows with 26% (128/489) of RHEV infections in animals, resulting in four human cases out of twenty-one globally. Phylogenetic analysis and genomic sequencing will be employed to gather global data, determine epidemiology, and assess geographical distribution. This information will enhance diagnostic accuracy, pathogenesis understanding, and help prevent cross-species transmission, particularly to humans.